Laplace Transform and Bessel Functions in Solving an Electrochemical Corrosion Problem - Victor Martinez-Luaces*; Mauricio Ohanian (Annals of Mathematics and Physics, 2025)
Abstract Electrochemical corrosion protection of metallic structures, particularly, in oil storage tanks, is a problem of great industrial importance. This paper proposes a mathematical model based on partial differential equations, which can be simplified to an ordinary differential equation with variable coefficients, under certain conditions. The latter is solved using Laplace transform, resulting in a solution expressed in terms of modified Bessel functions.